Mobilisasi Progresif Meningkatkan Status Hemodinamika Pada Pasien Kritis Di Intensive Care Unit: Literature Review - Rahmat Hidayat; Erna Julianti (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2023)
Patients treated in the Intensive Care Unit (ICU) are critical patients who are in a life-threatening condition due to failure or dysfunction in one or multiple organs accompanied by hemodynamic disorders. Critical patients in a state of decreased consciousness have limitations in mobilization, which have an impact on unstable hemodynamic status (Heart Rate (HR), Respiratory Rate (RR), oxygen saturation (Sa), and blood pressure. One of the interventions that can be done to deal with this is progressive mobilization. Objective: to identify research articles on the effect of progressive mobilization on hemodynamic status and the incidence of pressure sores in critically ill patients in the ICU. The method is a literature review, which analyzes scientific articles from 4 databases: Science Direct, Proquest, Ebscohost, and Google Scholar. Keywords progressive mobilization, hemodynamics, pressure sores. Inclusion criteria for research articles, 2016-2020, Indonesian and English. Obtained 7 articles using the PICO formulation. The research article analysis technique is in a table format containing the author, title, year, method (design, sample and analysis), and results. Based on 7 research articles obtained, it shows that there is an effect of progressive mobilization on hemodynamic status and the incidence of pressure sores in critically ill patients in the ICU. All articles show different results.